VIOLENCE AGAINST CHILDREN AND ADOLESCENTS: ANALYSIS OF THE TRAINING OF FUTURE GENERALIST DOCTORS IN THE FACE OF SUSPECTED CASES IN THE MUNICIPALITY OF RIO DE JANEIRO - RJ - Costa Silva, Lays; Alt Parente, Elizabeth; Beatriz Azevedo Barbosa Mambreu, Ana; Correa Ferreira, Cristiana; Bonatto Jansen Ferreira, Daniela; Cincinatus Dias dos Santos, Isabelle (Health and Society, 2024)
Introduction: Child violence is a public health problem and is defined as any type of action or omission that may harm physical or psychological integrity, freedom or the right to child growth and development. In Brazil, as provided for in article 227 of the Federal Constitution and article 13 of the Statute of the Child and Adolescent (ECA), abuse against children are the object of mandatory notification, predicting penalties for professionals who fail to communicate the cases of your knowledge. Since 2011, child violence, regardless of its type, has been part of the list of compulsory notification in Law 4.730/2011, implying the doctor the duty to notify, as well as to assume civil and criminal liability on the case . Objectives: To analyze the training of the students of the fifth and sixth year of the medical course regarding knowledge and conduct in the face of a suggestive picture of violence against children and adolescents in the various scenarios of practical action. METHODS: This is a quanti-quarter, transverse, exploratory characteristic descriptive study. As a method of data collection, the application of questionnaires containing open and closed questions, adapted from the questionnaire proposed by Dossi (2009), was used. The sending to students of the 5th and 6th year of medicine occurred electronically. The ethical criteria defined by Resolution No. 510 of the National Health Council (CNS), promulgated in 2016, were obeyed on research involving human beings, being respected voluntary participation and anonymity of the study population, using the free and informed consent form (Tcle). The research was submitted to the Research Ethics Committee (CEP) and obtained its approval. 4. Results/Discussion: A total of 40 (forty) answers was obtained. Regarding the participants’ profile, it was observed that 70% of participants are white ethnicity, 72.5% cisgender women and most aged 20 and 30 years old (77.5%). Students defined childhood violence broadly, recognizing it as any kind of physical, psychological and/or moral damage that can directly or indirectly compromise the physical or mental integrity of children. Among the types of child violence mentioned are physical, psychological and sexual aggression. A participant also stressed the importance of considering nutritional, vaccination and educational neglect. One third of the inmates reported having had some kind of experience in their clinical practices with situations suspected of child violence. Although most students (77%) consider themselves able to identify and communicate situations of violence, 95% say they are unaware of flows and protocols to follow. 5. CONCLUSIONS: Data reveals gaps in the preparation of students to deal with child violence. One third of them did not have classes or discussions on the subject, while 32.5% received only one class and 35% had up to 3 classes on the subject. These findings highlight the need to improve the training of professionals in the field, ensuring that they are prepared to deal with such situations, as well as promote the well-being of children in different situations of violence.